Enhancing nursing simulation education: A case for extended reality innovation - TAÇGIN, ZEYNEP (My University, 2023)
This concept paper explores the use of extended reality (XR) technology in nursing education, with a focus on three case studies developed at one regional university in Australia. Tertiary education institutions that deliver nursing curricula are facing challenges around the provision of simulated learning experiences that prepare students for the demands of real-world professional practice. To overcome these barriers, XR technology, which includes augmented, mixed, and virtual reality (AR, MR, VR), offers a diverse media platform for the creation of immersive, hands-on learning experiences, situated within virtual environments that can reflect some of the dynamic aspects of real-world healthcare environments. This document analysis explores the use of XR technology in nursing education, through the narrative and discussion of three applied-use cases. The collaboration and co-design between nursing educators and XR technology experts allows for the creation of synchronous and asynchronous learning experiences beyond traditional nursing simulation media, better preparing students for the demands of real-world professional practice.
Keywords: extended reality; nursing; educational technology; simulation education